2021
DOI: 10.3390/biom11091259
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Tricarboxylic Acid Cycle Metabolites in Kidney Diseases

Abstract: Mitochondria are complex organelles that orchestrate several functions in the cell. The primary function recognized is energy production; however, other functions involve the communication with the rest of the cell through reactive oxygen species (ROS), calcium influx, mitochondrial DNA (mtDNA), adenosine triphosphate (ATP) levels, cytochrome c release, and also through tricarboxylic acid (TCA) metabolites. Kidney function highly depends on mitochondria; hence mitochondrial dysfunction is associated with kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 181 publications
2
28
1
Order By: Relevance
“…Among metabolites associated with one-year eGFR, three (i.e., succinyl-CoA, succinate and fumarate) are part of the Tricarboxylic Acid (TCA) cycle. Numerous studies have shown that the mitochondria and TCA cycles are dysregulated at the renal level during AKI and CKD [16,17,[50][51][52]. We noticed that the estimated succinate levels were linked to a worse outcome, while the opposite was observed for fumarate.…”
Section: Discussionmentioning
confidence: 71%
“…Among metabolites associated with one-year eGFR, three (i.e., succinyl-CoA, succinate and fumarate) are part of the Tricarboxylic Acid (TCA) cycle. Numerous studies have shown that the mitochondria and TCA cycles are dysregulated at the renal level during AKI and CKD [16,17,[50][51][52]. We noticed that the estimated succinate levels were linked to a worse outcome, while the opposite was observed for fumarate.…”
Section: Discussionmentioning
confidence: 71%
“…Citric acid is an intermediate metabolite from the tricarboxylic acid (TCA) cycle being synthesized from acetyl-CoA and oxaloacetate. These metabolic pathways occur in the mitochondrial matrix, which is responsible for cellular energy production due to the adenosine triphosphate (ATP) generation [ 28 ]. Kidney cells are rich in mitochondria and are highly dependent on this organelle’s function due to their high energy demand [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, some studies revealed that the severity and progression of CKD is associated with mitochondrial dysfunction and markers of oxidative stress [ 29 , 30 ]. If mitochondrial activity is unbalanced, there is an increase in oxidative stress and the inflammatory state, which may be more pronounced in CKD2 patients [ 28 , 29 , 30 ]. Hence, mitochondrial and TCA cycle alterations can be associated with an accumulation of serum citric acid, which is a precursor of several other metabolites [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we observed, the increase in renal fatty acids synthesis enzymes consequently increases the plasma concentration of fatty acids ( Table 3 ), as was previously seen in CKD patients [ 9 ]. In addition, the Krebs cycle decreased due to mitochondria damage, increasing acetyl-CoA concentrations and providing more substrates for lipid synthesis [ 60 ]. Indeed, kidney biopsies from CKD patients showed reduced mRNA levels of Krebs cycle proteins, which is associated with lower levels of AMP-activated protein kinase (AMPK) and PGC-1α [ 50 , 55 , 61 , 62 , 63 ], the two key regulators of mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…(1) In kidney of 5/6 nephrectomy (5/6Nx), adenosine triphosphate (ATP) levels are reduced, attributed to the decrease in the activity of electron transfer system (ETS) elements complex I (CI), CIII, and CIV, and ATP synthase [ 34 ]. (2) The decrease in the ETS reduces β-oxidation [ 18 ], which along with the reduction in the Krebs cycle, leads to (3) acetyl CoA accumulation [ 60 ]. This acetyl CoA is used for (4) fatty acids (FA) synthesis, inducing (5) lipid accumulation, and latter (6) FA release into the bloodstream, particularly (7) palmitoleic acid, which increases in the bloodstream and might (8A) reenter the kidney via a cluster of differentiation 36 (CD36), contributing to lipid accumulation [ 9 ].…”
Section: Figurementioning
confidence: 99%